Social and Emotional Skills in at-Risk Adolescents through Participation in Sports - Andreia P. Teques; Rita F. de Oliveira; Michala Bednarikova; Maurizio Bertollo; Grzegorz Botwina; Anastasiya Khomutova; Hamit Emir Turam; İlknur Dinç; Marcos López-Flores; Pedro Teques (MDPI AG, 2024)
(1) Background: Adolescents who are under the care of child and youth institutions are vulnerable due to factors that can include disruption to family structure or education and adverse experiences. They often experience poor or unstable support systems, leaving them at risk of delinquency. In this context, sports engagement may provide a stable structure and have positive effects in this population. Therefore, the purpose of this study was to explore the perceptions, knowledge, beliefs, and behaviors regarding social and emotional skills among at-risk adolescents, with a specific focus on their engagement in sports. (2) Methods: Ninety-six adolescents aged 12 to 17 years (66 female, 30 male), residing in child and youth care institutions across Italy, Portugal, the UK, and Turkey, participated in this study. The participants were divided into 14 focus groups, each with six to eight participants of similar ages. (3) Results: Thematic analysis revealed four main themes: Emotional causes of behavioral problems; Emotional skills to regain control; Social support makes sports worthwhile; Sport as a socio-emotional resource. (4) Conclusions: The study findings highlight that although sports create many challenging emotional situations for these adolescents, they also provides resources that may help them cope with their emotions within and beyond sports.